In vitro infection with Theileria parva is associated with IL10 expression in all bovine lymphocyte lineages - McKeever, Declan J.; Nyanjui, J.K.; Ballingall, Keith T. (Wiley, 1997)
The protozoan parasite Theileria parva infects and transforms bovine lymphocytes, giving rise to a fatal lympho-proliferative condition known as East Coast fever. Although immune cattle mount strong cytolytic T. lymphocyte responses to the parasite, naive animals appear unable to respond and develop severe immunopathological lesions. We have investigated the patterns of cytokine mRNA expressed by 19 bulk and cloned parasite-infected lymphoblast cell lines using a multiplex PCR system. Considerable variation was observed in the cytokine profiles of these lines and only IL10 was universally expressed. Investigation of cloned lines representing the major bovine lymphocyte populations failed to reveal a lineage-specific pattern of cytokine mRNA expression that could be associated with infection. Nonetheless, analysis of a CD4 - T cell clone before and after transformation with the parasite indicated that infection does alter the pattern of cytokine expression, with apparent upregulation of IL10. These observations raise the possibility that IL10 derived from infected cells may influence the immune responses of naive cattle to challenge.